Revealing facts behind spray dried solid dispersion technology used for solubility enhancement - Patel B.B.; Patel J.K.; Chakraborty S.; Shukla D. (My University, 2025)
Poor solubility and bioavailability of an existing or newly synthesized drug always pose challenge in the development of efficient pharmaceutical formulation. Numerous technologies can be used to improve the solubility and among them amorphous solid dispersion based spray drying technology can be successfully useful for development of product from lab scale to commercial scale with a wide range of powder characteristics. Current review deals with the importance of spray drying technology in drug delivery, basically for solubility and bioavailability enhancement. Role of additives, selection of polymer, effect of process and formulation parameters, scale up optimization, and IVIVC have been covered to gain the interest of readers about the technology. Design of experiment (DoE) to optimize the spray drying process has been covered in the review. A lot more research work is required to evaluate spray drying as a technology for screening the right polymer for solid dispersion, especially to overcome the issue related to drug re-crystallization and to achieve a stable product both in vitro and in vivo. Based on the recent FDA recommendation, the need of the hour is also to adopt Quality by Design approach in the manufacturing process to carefully optimize the spray drying technology for its smooth transfer from lab scale to commercial scale. © 2013 King Saud University.